Online training resources to aid therapeutic radiographers in engaging in conversations about physical activity and diet: A mixed methods study. Issue 1 (February 2022) - Pallin, N.D.; Webb, J.; Brown, L.; Woznitza, N.; Stewart-Lord, A.; Charlesworth, L.; Beeken, R.J.; Fisher, A.
Abstract: Introduction: This study explored changes in therapeutic radiographers' (TRs) self-reported knowledge and skills to engage in conversations about physical activity and diet with people living with and beyond cancer following completion of publicly available online courses. Methods: Participants were randomly assigned to two of five online courses that aim to support health professionals to engage in conversations about physical activity and diet in the oncology setting. Participants rated their agreement with 18 statements related to the COM-B (capability, opportunity and motivation-behaviour) model components following completion of an online course on healthy diet (n = 16) and physical activity (n = 21). Semi-structured telephone interviews (n = 21) were also conducted. Analysis of the interviews was guided by the Theoretical Domains Framework. Results: Overall, the online courses were acceptable and the TRs in this study self-reported improved COM to deliver advice on physical activity and diet. The inclusion of the evidence and scientific rationale on the benefits of diet and physical activity, and also guidance on how to start conversations with patients were highlighted as important features of the courses. Suggestions for adaptations to the nutrition courses included the need for content that accounts for the side effects cancer patients experience while undergoing treatment. To support the implementation of training and the delivery of advice on these topics, multi-disciplinary working, organisational support and guidance around professional role boundaries were highlighted as important. Conclusion: Current publicly available online courses on physical activity and diet for oncology health professionals can reduce some barriers among TRs to providing advice to those living with and beyond cancer. Implications for practice: Existing online training courses could be used to support TRs to deliver physical activity and dietary advice in practice. Findings show that these courses can be disseminated within radiotherapy departments. The results also highlight a number of important considerations for the implementation of brief health behaviour advice and online training interventions on physical activity and diet within cancer care.